Seasonal Shift in Storm Surges at Brest Revealed by Extreme Value Analysis. Issue 12 (27th December 2021) - Reinert, Markus; Pineau‐Guillou, Lucia; Raillard, Nicolas; Chapron, Bertrand
Abstract: Global warming changes the Earth's climate in different ways, in particular it influences extreme weather events like storms. Strong storms cause large surges and thus have a signature in the sea level record. While previous studies focused on long‐term changes of storm surge amplitude or frequency, changes in the timing of extreme surge events have not been investigated so far. We employed the more than 150 yr long tide gauge record of Brest (France) and found a distinct shift of storm surge timing between the years 1950 and 2000. This caused extreme events to happen about three weeks earlier during the year. We developed for this study two different methods based on statistical extreme value analysis; both methods show this shift of the seasons consistently. Furthermore, by analyzing eight additional stations, we found evidence that this timing shift happened similarly over a large part of the European Atlantic coast. Therefore, we speculate that our measured shift is part of a large‐scale climate process. Plain Language Summary: Climate change leads to an increase of the sea level all over the world. This means not only that the average sea level rises, but also that extreme sea levels become higher, which presents a major threat for coastal communities. To prepare for this growing natural hazard, it is important to understand how extreme sea levels evolve in a warming climate. One of the best places to study this is the harbor of Brest, France, which has one of the longest sea level records in the world (over 150 yr). From this time series, we extracted the surge, which is the part of the sea level that is created by large‐scale atmospheric forcing, like storms. We used two statistical methods to analyze the extreme surge levels in Brest, and we found that between 1950 and 2000, the season of large surge levels shifted forward. In 2000, extreme storm surge events happened three weeks earlier than 50 yr before. We then analyzed sea level records of other stations and found the same shift over large parts of the European Atlantic coast. So we conclude that this shift of the extreme surge season might be the signature of a large‐scale climate process. Key Points: Extreme storm surge events occurred three weeks earlier in Brest in the winter 2000 than in the 1950s Shift of winter storm surge timing was calculated consistently with two statistical methods Analysis of additional stations in Europe suggests a large‐scale process